Pengembangan Wisata Bukit Batu Galugur sebagai Pariwisata Berkelanjutan Desa Bina Bhakti - Hapsawati Hapsawati; Laely Fuad Magfiroh; Ageng Zikriana; Fuad Sultoni; Siti Apriyani Rosu; Nurwahidah (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2024)
Bukit Batu Galugur is a hill tour located in Bina Bhakti village in Sematu Jaya district, Lamandau regency, Central Kalimantan. in addition to being a tourist spot in Bukit Batu Galugur, there are several places for children and adults to play and also some culinary that can be felt by the community and provide new opportunities for business tourism, hiking, green energy-friendly transportation. increase revenue to help the local economy become more independent, and strengthen local production. The approach used in this study is a qualitative descriptive method through a review of literature related to the development of local tourism village of Bukit Batu Galugur as part of Sustainable Tourism Development. The results of this study the usefulness that can be taken from the creation of sustainable tourism Bukit Batu Galugur are: sustainable tourism operations can help local communities by creating new business possibilities and improving the economy. The purpose of development is to promote the economic growth of the community while preserving and protecting the environment, especially renewable resources